Advanced Maternal Age and the Risk of Major Congenital Anomalies - Goetzinger, Katherine R.; Shanks, Anthony L.; Odibo, Anthony O.; Macones, George A.; Cahill, Alison G. (American Journal of Perinatology, 2017)
Objective This study aims to determine if advanced maternal age (AMA) is a risk factor for major congenital anomalies, in the absence of aneuploidy.Study Design Retrospective cohort study of all patients with a singleton gestation presenting for second trimester anatomic survey over a 19-year study period. Aneuploid fetuses were excluded. Study groups were defined by maternal age ≤ 34 and ≥ 35 years. The primary outcome was the presence of one or more major anomalies diagnosed at the second trimester ultrasound. Univariable and multivariable logistic regression analyses were used to estimate the risk of major anomalies in AMA patients.Results Of 76,156 euploid fetuses, 2.4% (n = 1,804) were diagnosed with a major anomaly. There was a significant decrease in the incidence of major fetal anomalies with increasing maternal age until the threshold of age 35 (p < 0.001). Being AMA was significantly associated with an overall decreased risk for major fetal anomalies (adjusted odds ratio: 0.59, 95% confidence interval: 0.52–0.66). The subgroup analysis demonstrated similar results for women ≥ 40 years of age.Conclusion AMA is associated with an overall decreased risk for major anomalies. These findings may suggest that the “all or nothing” phenomenon plays a more robust role in embryonic development with advancing oocyte age, with anatomically normal fetuses being more likely to survive.
Keywords: advanced maternal age; aneuploidy; congenital anomalies; fetal structural malformation